miRNA based biomarkers for the early diagnosis of Echinococcus granulosus in experimentally infected dogs - Celik, Figen; Tektemur, Ahmet; Simsek, Sami (Elsevier, 2023)
Cystic echinococcosis, which is caused by the Echinococcus granulosus. Carnivores, as final hosts, contain adult tapeworms in the small intestine, and a variety of mammals, including humans, harbor the metacestod. This study was designed to investigate the miRNA-based biomarkers for early and accurate diagnosis of E. granulosus in experimentally infected dogs. A liver with an obvious hydatid cyst was obtained from a slaughterhouse and then protoscoleces were collected. Following, viable protoscoleces were administred to three experimental dogs (ED1, ED2 and ED3) and another uninfected control dog (UCD) was kept as control without infection. Stool samples of all groups were collected during 50 days from the beginning of the experimental infection and stored at - 80 degrees C till work. Total miRNA was isolated from all individual stool samples. The qRT-PCR method was used to determine the differences in the expression levels of E. granulosus specific miRNAs which were egr-let-7-5p, egr-miR-2b-5p, egr-miR-71-5p and egr-miR-125-5p. All miRNAs were found to be expressed from the first day in all infected dogs. In the stool samples of the UCD, the egr-miR-71-5p was detected, while the other miRNAs (egrlet-7-5p, egr-miR-2b-5p, egr-miR-125-5p) were not expressed. The expression of egr-let-7-5p and egr-miR125-5p was significantly increased in ED1 compared to UCD on all days. In particular, for the first time, the expression levels of egr-let-7-5p and egr-miR-125-5p increased significantly between days 15 and 19. Similarly, the increase in let-7-5p and miR-125-5p expression was statistically significant in ED2. In ED3, egr-let-7-5p, egrmiR2b-5p and egr-miR-125-5p expressions were significantly increased on all days. In particular, egr-let-7-5p expression levels increased significantly for the first time between days 15 and 19. In addition, egr-mir-125-5p expression levels were found to increase at a high level for the first time on day 16. In conclusion, especially egrlet-7-5p and egr-miR-125-5p can be used as early diagnostic biomarkers in dogs infected with E. granulosus.
Keywords: Echinococcus granulosus; Dog; MiRNA; Diagnosis; Stool